The effects of linear energy density and gas environment on droplet spatter characteristics and dynamics during selective laser melting - Guang Yang; Qi Liu; Da An; Xiangming Wang; Ranliang Wu; Han Xie (Materials & Design)
The spatter produced during SLM significantly impacts the interaction between the laser and the powder bed, with linear energy density and the gas environment being key factors. Utilizing high-speed imaging technology and a novel image processing method, we developed a new spatter feature extraction algorithm to analyze the number, area, angle, and speed of the spatter under different energy densities and protective gas directions. The results indicate that as the linear energy density increases from 0.15 J/mm to 0.3 J/mm, the number and intensity of the spatter initially decrease and then increase. Comparative analysis shows that droplet spatter is significantly reduced when applying protective gas opposite to the scanning direction (GD-L) compared to along the scanning direction (GD-W). This study establishes a quantitative relationship between linear energy density, gas direction, and droplet spatter behavior. The mechanism of droplet spatter is discussed and divided into three categories. Predicting the recoil pressure and horizontal distance of spatter. It provides a theoretical reference for the parameter design and control of linear energy density and gas direction in the SLM process.